2022
DOI: 10.3390/su14074173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cement Kiln Dust and Cement on Cold Mix Asphalt Characteristics at Different Climate

Abstract: Cold bitumen emulsion mixtures (CBEMs) are made up of the same materials that are used in hot mixes. However, asphalt emulsion and water are used in such mixes. To date, many countries are still not using these mixes as a structure layer. This can be attributed mainly to their low resistance to rainfall, long curing time and low early strength. The addition of cementitious filler to CBEMs as a clean paving material is a potential technique to achieve superior mechanical qualities. The aim of this research is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In addition, the utilization of CKD in these applications is considered safe and is not accompanied by any adverse effects on health or the environment alike, according to what was stated by The United States environmental protection agency (EPA) [8]. Accordingly, using CKD in various industrial applications contributed to a positive turning point in reducing its adverse economic or environmental effects, as was evident in several investigations [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…In addition, the utilization of CKD in these applications is considered safe and is not accompanied by any adverse effects on health or the environment alike, according to what was stated by The United States environmental protection agency (EPA) [8]. Accordingly, using CKD in various industrial applications contributed to a positive turning point in reducing its adverse economic or environmental effects, as was evident in several investigations [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…Previous investigations have shown that cementitious materials like ordinary Portland cement (OPC) and rapid-setting cement might be used to improve the mechanical properties of EACMs (Kadhim et al, 2018;Abdel-Wahed et al, 2022;Deb and Singh, 2022;Shen et al, 2022). According to certain research, cement can accelerate the demulsification of the asphalt emulsion and increase the EACMs' early age strength by producing cement hydrates (Wang et al, 2015;Dołżycki et al, 2017;Du, 2018;Gan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The effective utilization of various mineral fillers such as lime [9], hydrated lime [10], limestone powder [11], fly ash [12] and cement [13] to improve the strength of asphalt mixtures has been investigated in various studies. In particular, Portland cement has demonstrated better effectiveness as a filler material [14]; however, on account of high CO 2 emissions associated with cement manufacturing, researchers are constantly looking for alternate environment-friendly filler materials [15].…”
Section: Introductionmentioning
confidence: 99%